1979
DOI: 10.1073/pnas.76.7.3401
|View full text |Cite
|
Sign up to set email alerts
|

Sustained growth and three-dimensional organization of primary mammary tumor epithelial cells embedded in collagen gels.

Abstract: We have develo ed a method for embedding cells within a collagen matrix which allows sustained growth of mouse mammary tumor epithelial cells in primary culture. A characteristic and reproducible pattern of organization and growth occurs: the cells rearrange themselves and produce duct-like structures extending into the matrix, resulting in a three-dimensional outgrowth. Autoradiography showed continuous [3H] The limited in vitro growth capacity of mammary epithelial cells in conventional primary culture in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(103 citation statements)
references
References 14 publications
4
98
0
1
Order By: Relevance
“…The use of primary mammary cell cultures for the analysis of cell growth has been limited to studies of [aH]thymidine incorporation in short-term cultures, because of the inability to maintain mammary cells in long-term cultures. Due to recent developments in the cultivation of mammary cells using stromal collagen matrices (45), it became possible to maintain sustained growth and thus to determine the effect of various hormones and growth promoting factors by estimating the increase in cell number (20,32,46).…”
Section: Hormonal Requirements For Cell Proliferationmentioning
confidence: 99%
“…The use of primary mammary cell cultures for the analysis of cell growth has been limited to studies of [aH]thymidine incorporation in short-term cultures, because of the inability to maintain mammary cells in long-term cultures. Due to recent developments in the cultivation of mammary cells using stromal collagen matrices (45), it became possible to maintain sustained growth and thus to determine the effect of various hormones and growth promoting factors by estimating the increase in cell number (20,32,46).…”
Section: Hormonal Requirements For Cell Proliferationmentioning
confidence: 99%
“…For instance, cells isolated from cavitary organs such as mammary epithelial cells (YANG et al, 1979), submandibular epithelial cells (YANG et al, 1982), Madin-Darby canine kidney (MDCK) cells (HALL et al, 1982), and capillary endothelial cells (MONTESANO et al, 1983) reconstitute cavitary structures when they are cultured in a three-dimensional collagen gel. As for the thyroid gland, CHAMBARD and his co-workers (1981) reported that thyroid follicular epithelial cells as well reconstitute the follicular structure when they are cultured in a collagen gel.…”
Section: Resultsmentioning
confidence: 99%
“…4) Further staining is possible, including immunohistochemical staining and TUNEL. 5) The use of collagen gel as an extracellular matrix mimics the condition in vivo, [24][25][26] except in the case of small cell lung cancer cells that become resistant to chemotherapeutic agents when they adhere to an extracellular matrix. 27) In cancer chemotherapy, induction of apoptosis in cancer tissue without affecting normal cells is a major objective, so a simple and reproducible method is required to identify apoptosis in experimental studies of cancer chemotherapy.…”
Section: Discussionmentioning
confidence: 99%